Is the Annual Confidential Report system effective? A study of the government appraisal system in Gujarat, India. Issue 1 (December 2016) - Purohit, Bhaskar; Martineau, Tim
Abstract Background Effective performance appraisal systems can not only motivate employees to improve performance but also be important for the performance of organizations. However, the appraisal systems in civil services called the Annual Confidential Report (ACR) systems can be ineffective and do not contribute to employees' learning and development. With this background, the current study aimed at understanding the ACR system and assessing its effectiveness. The research aims to contribute in filling the knowledge gap in the existing literature on the need as to why the ACR system in civil services is an important human resource management (HRM) function. Methods The analysis is based on policy review to understand the extant appraisal-related rules and policies. Nineteen in-depth interviews with medical officers (MOs) working with the government health department of Gujarat, India, were conducted. The main objective of the research was to assess the effectiveness of the actual appraisal system called or referred to as the ACR as perceived by MOs. Thematic framework approach was used to analyze qualitative data using NVIVO 9. Themes were built around five features of an effective appraisal system, i.e., purpose, source, feedback quality, link of the ACR system with other human resource functions, and administrative effectiveness. Results The five features of the effective appraisal system studied in the current research (purpose, source, feedback quality, link of ACR system with other HRM functions, and administrative effectiveness) indicate that the overall appraisal system is ineffective. The overall appraisal system was perceived to be subjective and one directional in character by the study respondents. Furthermore, respondents perceived the appraisal system to be a ritual and where MOs hardly got to know about their performance, especially good performance. Hence, the feedback loop, an important feature for an effective appraisal system, was absent. The overall ACR system functions in isolation with no link to other HRM functions such as training and counselling, and a weak link with salary administration and promotion. Conclusions Addressing the five features or domains of an effective appraisal system can lead to improved perceived fairness MOs have on the current appraisal system which may further influence the satisfaction and motivation positively. Improved motivation and satisfaction with the appraisal system can influence two important human resource for health-related outcomes, i.e., performance and retention.